1708d Alteration of immune cells in silicosis: roles in development of autoimmunity and lung fibrosis. (24th April 2018) - Otsuki, T; Hayashi, H; Lee, S; Matsuzaki, H; Kumagai-Takei, N; Yoshitome, K; Nishimura, Y; Fujimoto, W
Abstract : In addition to lung fibrosis, silicosis (SIL) patients often suffer from complicated autoimmune disorders such as rheumatoid arthritis, systemic sclerosis and anti-neutrophil cytoplasmic antigen-related vasculitis/nephritis. Thus, chronic and recurrent exposure to silica particles located in the lung and lymph nodes can result in alterations in the function of immune cells, which can lead to the dysregulation of autoimmunity in addition to the development of lung fibrosis. Regarding B cells which produce various antibodies, in SIL many autoantibodies are often detected in autoimmune diseases, and specifically autoantibodies against apoptosis-related molecules. Responder T helper (rTh) cells which respond to foreign and auto-antigens have been reported to survive longer and have apoptosis inhibited. Additionally, regulatory T (Treg) cells seem to proceed to early apoptosis. This imbalance between rTh and Treg cells may make SIL patients prone to autoimmune disorders. Although the role of dendritic cells (DCs) including alveolar macrophages and T helper 17 (Th17) cells in the dysregulation of immune tolerance in SIL remains poorly understood, these cells play a role in pulmonary inflammation and the development of fibrosis via specific receptor and signalling molecules. Further studies are required to delineate the roles of DCs and Th17 cells in the disturbance of autoimmunity found in SIL, and investigation of the immunological alterations that lead to autoimmune dysregulation may assist in the recognition, prevention, and treatment of complicated autoimmune diseases found in SIL.